Research of Gamma Radiation Background in Šiauliai - Vaičys, Edvinas; Klimas, Robertas; Tričys, Vaclovas (Jaunųjų mokslininkų darbai, 2018)
In the article, the authors identify sources of ionizing gamma radiation, their types, possible exposure to humans and the environment. In addition it discusses the external and internal exposures of natural origin. The most important concepts and terms used in radiological measurements are presented. The results of background research on gamma radiation in Šiauliai are analysed. The values of gamma radiation background in town areas, in various buildings and in building materials, and changes in the gamma radiation background in different floors of residential buildings were measured. In addition, the authors measured background radiation values of gamma in water bodies and drinking water in Šiauliai city. In the course of the study, the gamma radiation background in Šiauliai city districts varied from 0.07 μSv/h to 0.13 μSv/h. Gamma radiation background values can depend on the soil composition and the works carried out in previous years. Measurement data is systematized and visually presented. It has been established that the gamma radiation values in the investigated residential houses, materials and drinking water did not exceed the permissible exposure doses established in hygiene norms. The paper presents conclusions about gamma radiation background research results.
Keywords: gamma rays; radiation background; radiation measurement; radon; radiation doses